On the Division to Nonexistent and Void Contracts in Domestic Law - Miščević, Nikolina B.; Radovanović, Sanja M. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Summary: In the Law on Obligations, in the part that regulates invalidity of contracts only void and voidable contracts are mentioned. However, domestic theory often speaks of the further division of the void contracts to inexistent contracts and void contracts in the narrow sense. While some deny any practical significance to this division, others point out the necessity of its existence. The paper analyzes the perceptions of domestic authors on this division, the arguments made in favor of distinguishing nonexistent from void contracts, as well as the rules of the Law on Obligations, in order to examine the need for nonexistent contracts as a special type of invalid contracts.            Keywords: void contracts, nonexistent contracts, conversion of contracts, invalidity of contracts.